The Origins of Terrorism: Cross-Country Estimates on Socio-economic Determinants of Terrorism - Andreas Freytag; Jens J. Krüger; Daniel Meierrieks (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
As a prerequisite of an appropriate anti-terror strategy, it is indispensable to assess the underlying causes of terror. We examine social and economic conditions in the country of origin of terrorist attacks, claiming that low opportunity costs of terror, e.g., approximated by slow growth and poor institutions raise the likelihood of terror and the willingness in the population to support terror. Using a negative binomial regression model, we are able to show that unfortunate socio-economic conditions in a country are likely to reduce the opportunity costs of potential terrorists and increase the number of terrorist attacks originating from a specific country. Interestingly, this effect is particularly relevant after a certain level of development has been reached. We therefore distinguish between several broad country groups, namely the OECD, Europe and Islamic countries.
Keywords: P16; F15; C25; 330; terror attacks; openness; discrete choice analysis; institutions